2014
DOI: 10.5334/jbr-btr.87
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele of the appendix : a case report and review of the literature

Abstract: Mucocele of the appendix is a descriptive term of a distended, mucus-filled appendix caused by various conditions, both benign and malignant. Computed tomography is the imaging modality of choice. Correct pre-operative diagnosis is important because of the possibility of peroperative rupture and subsequent development of pseudomyxoma peritonei. It is the task of the radiologist to alert the clinician and surgeon to the presence of this entity, the potential associated complications and possible signs of malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The clinical manifestations of perforated LAMN are more pronounced compared to non‐perforated LAMN, and although others have reported that 1/3 of patients with LAMN are asymptomatic, our study showed that the clinical manifestations include abdominal pain, bloating, abdominal discomfort, and increased abdominal girth. Many patients with mucinous appendiceal tumors are misdiagnosed as acute appendicitis, 24,25 and in our study, 27 patients were misdiagnosed preoperatively as appendicitis.…”
Section: Discussionmentioning
confidence: 51%
“…The clinical manifestations of perforated LAMN are more pronounced compared to non‐perforated LAMN, and although others have reported that 1/3 of patients with LAMN are asymptomatic, our study showed that the clinical manifestations include abdominal pain, bloating, abdominal discomfort, and increased abdominal girth. Many patients with mucinous appendiceal tumors are misdiagnosed as acute appendicitis, 24,25 and in our study, 27 patients were misdiagnosed preoperatively as appendicitis.…”
Section: Discussionmentioning
confidence: 51%
“…Post-operative complications include intestinal obstruction, GI bleeding, fistula formation, volvulus and PP related to iatrogenic rupture of the mucocele [20]. Thus, the vast majority of investigators support conventional surgical intervention as the treatment of choice for AM, as the tissues should be handled carefully intra-operatively.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The severest complication of the appendicular mucocele perforation is the pseudomyxoma peritonei (mucinous ascites), if there is underlying neoplastic etiology. [18,19]…”
Section: Appendicular Mucocele/low-grade Cystic Tumormentioning
confidence: 99%